Uterine Natural Killer Cell and Human Leukocyte Antigen-G1 and Human Leukocyte Antigen-G5 Expression in Vaginal Discharge of Threatened-Abortion Women: A Case-Control Study - Saeideh Sadat Shobeiri; Zahra Rahmani; Hadi Hossein Nataj; Hossein Ranjbaran; Masoud Mohammadi; Saeid Abediankenari (Journal of Immunology Research)
The immunotolerant human leukocyte antigen-G (HLA-G) molecules have a major role in fetal-maternal tolerance during pregnancy. Interaction between these molecules and uterine natural killer (uNK) cells inhibitory receptors prevents NK cell invasion against fetus trophoblast cells. The aim of this study was to evaluate the percentages of uNK cells and HLA-G1 and HLA-G5 isoforms expression in vaginal discharge of threatened-abortion women in comparison with control. In a case-control study, we investigated 30 threatened-abortion women with bleeding or spotting less than 20 weeks of pregnancy as compared to 30 normal pregnant women. uNK cells percentage was assessed by flow cytometry. Furthermore, we evaluated HLA-G1 and HLA-G5 isoforms expression by Real-Time PCR in these groups. The results of this study showed that threatened-abortion women had increased uNK cells and decreased T cells percentage in vaginal discharge in comparison with normal pregnant women (p=0.01, p=0.003, resp.). In addition, HLA-G1 isoform had lower expression in threatened-abortion women in comparison with control group p=0.0001. The increase of uNK cells level with the decrease of HLA-G expression in vaginal discharge of threatened-abortion pregnant women is an indicator of mother’s immune dysregulation. It is concluded that HLA-G expression level with uNK cells percentage can be determined as a diagnostic marker for threatened-abortion women.